Interpretasi Surah Yâsîn [36]: 31-40 Perspektif Quraish Shihab: Studi Komparatif Antara Tafsir Tulis dan Lisan - Arwita, Ulya; Wardatutsaniyah, Tiara; Amru, Khobirul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
In the world of Qur'anic exegesis, surah Yâsîn is considered as one of the surahs that has its own specialty. Many scholars have tried to understand and interpret the deep meaning contained in it. One of the leading figures in the world of interpretation is Quraish Shihab, a well-known Muslim scholar who also made a valuable contribution in interpreting Surah Yâsîn. In this study, the author tries to compare between M. Quraish Shihab's written interpretation contained in Tafsir al-Mishbah and his oral interpretation documented on the YouTube digital platform. In this research, the author uses the type of Library Research and uses qualitative research methods. This study found three main points that distinguish between Quraish Shihab's written and oral interpretations in interpreting surah Yâsîn [36]: 31-40. First, in the written interpretation, references and references are included in detail, while in the oral interpretation, references are not explained. Second, in the written interpretation, the linguistic aspects are explained in detail, including the origin of the word and its meaning, while in the oral interpretation, the meaning of the word is explained with language that is easy to understand and in accordance with the context at that time. Third, written interpretation uses standardized language and is in accordance with the KBBI, requiring an understanding of sentence structure and language norms, while oral interpretation uses casual language that is easy to understand, allowing direct interaction with the interpreter.